The Complete and Original Norwegian Folktales of Asbjørnsen and Moe - Asbjørnsen, Peter Christen, 1812-1885; Moe, Jørgen Engebretsen, 1813-1882 (University of Minnesota Press, 2019)
"New, modern English translation of the folk tales collected by Peter Christen Asbjornsen and Jorgen Moe, which was first published in Norway in 1841, and a second edition in 1852"--